A Brief Review on Thermal Metamaterials for Cloaking and Heat Flux Manipulation. Issue 2 (25th November 2019) - Peralta, Ignacio; Fachinotti, Víctor D.; Álvarez Hostos, Juan C.
Abstract : Progress in material science has allowed the control of different physical fields in a manner that would be unachievable with ordinary materials. The development of engineered materials (the so‐called metamaterials) to control the conductive heat flux has revolutionized the manner of manipulating thermal energy and allowed the possibility of guiding the heat flux in ways difficult to accept for human intuition. Herein, a brief review regarding the recent progress and developments in thermal metamaterials conceived to perform several conductive heat flux manipulation tasks is provided. Deeply theoretical discussions concerning design methodologies are left a side, and the focus is made on the design and manufacturing feasibility of metamaterials for thermal cloaking and camouflage, heat flux concentration, and inversion, among other applications that lead to the next generation of thermal devices. Abstract : Herein, a brief review regarding the recent progress and developments in thermal metamaterials for conductive heat flux manipulation tasks is provided. Deeply theoretical discussions concerning design methodologies are left a side, and the main focus is made on the design and manufacturing feasibility of metamaterials for cloaking and camouflage, heat flux concentration, and inversion, among other applications.